Influence of drought stress on pollen viability and fertility - Hassan, Amira (2019)
Pollen viability is important in fertilization. Drought is one of the greatest stresses that affects food security (Wilhite et al, 1985). Yield loss vulnerability is closely correlated to pollen viability, with a significant reduction in pollen viability having a major impact on seed set. Genes involved in this process still are largely unknown. In Arabidopsis thaliana the expression of thirty genes, before and after pollen mitosis I associated with drought stress were examined using qRT-PCR under severe drought stress. Some genes showed specific expression patterns and regulation to drought at specific stage of pollen development. A subset of seven genes that showed altered expression in the anther during drought stress were studied by modifying their expression by knock out and overexpression lines, the candidate genes have the following locus identifiers: AT1G52570, AT4G36600, AT3G28980, AT2G24450, AT3G20220, AT3G23770 and AT1G63060. The overexpression lines of AT3G20220 displayed pleiotropic phenotype such as extreme dwarf, short stamen filament, low number of pollen grains, stem architecture and internode defects, changes in the inflorescence branch angles. AT1G52570 displayed an early flowering phenotype. AT3G23770 has a role in callose wall degradation and exhibited pleiotropic phenotype such as early anther dehiscence, internode defects, siliques and inflorescence pattern defect. Other lines showed impacts on flowering time and male fertility. Selected T-DNA insertion/knock out lines exhibited short siliques and inviable pollen (AT3G20220, AT2G24450 and AT4G36600).